Studying the Status of Biological and Physico-Chemical Indicators of Swimming Pools of the City Kermanshah (Iran) in 2016 - Mojtaba Afsharnia (Journal of Global Pharma Technology, 2017)
Swimming pools are the most attractive and popular of sports centers. Swimming has constructive effects on human physical and mental health care and lack of proper sanitation and disinfection Regulations of water in swimming pools is led to health problems and infectious disease transmission among swimmers. The aim of this study was to evaluate and compare the results of swimming pools in Kermanshah with the national standards. This study was descriptive-sectional and carried out in 2016 in 24 active pools in Kermanshah city by collecting statistics. In the survey in addition of the characterization of Public Pools Through interviews, heterotrophic bacteria, fecal coliforms, Pseudomonas aeruginosa, Staphylococcus aureus and physicochemical parameters such as residual chlorine, turbidity were assessed in the sampling sites and were recorded in the relevant forms. All calculations were performed with SPSS software (version 16) and statistical significance was considered 0.05. The results showed that from 99 samples in 15.2% of Pseudomonas aeruginosa has exceeded the standard level. In addition, 17.2% Staphylococcus aureus, 15.2% and the amount of fecal coliform, 17.2% bacteria heterotroph and 17.2% of residual chlorine levels were out of the standard limit. According on the results, residua chlorine, Staphylococcus aureus, Pseudomonas aeruginosa, fecal coliform, heterotroph bacteria indicators had the minimum compliance with standard levels which indicates the need for continuous monitoring of physical, chemical and biological indicators of water as well as filtration and disinfection of water. It also recommended alternative antibiotics.Keywords: biological, physical, chemical, swimming pool, Kermanshah, Iran